Press Freedom And Hoax: Democracy Anomaly - Ibnu Sina Chandranegara (NOMOI Law Review, 2020)
AbstractAfter the collapse of the New Order regime, the hope of a more realized configuration gave freedom of approval through apress. However, the freedom obtained by the Press is currently full of negatives, namely news of false news that is increasing. The method used in this study is a normative juridical legal research method. According to the results of the 2018 Edelman Trust Barometer survey, seven out of 10 people in the world were worried that fake news would be used as "weapons". In Indonesia alone, 76 to 80 percent of the public is worried about using hoaks as a weapon to create instability in the country. These findings indicate that there are challenges from democratic reform and post-reform law enforcement. This paper discusses the solution to the legal aspect of dealing with the rise of false news as an effort to protect democracy and freedom of information.Keywords: Press Freedom, Law Enforcement, Democracy.